Multi-Objective Model for End-Of-Life Tires Reverse Logistics: Enhancing Sustainability Through a Techno-Political Framework - Espinoza-Perez, A; Castañeda-Rodriguez, I (Elsevier Ltd, 2025)
The management of End-of-Life Tires (ELT) presents a growing concern about environmental pollution that has led to a tightening of legislation worldwide. One approach gaining attention is Extended Producer Responsibility (EPR), which makes producers responsible for the life-cycle management of their products. This work introduces a multi-objective optimization model that supports decision-making through the integration of a techno-political framework to enhance traditional sustainability assessment, studying the impact of introducing collection goals, valuation quotas and emerging valorization technologies. A Chilean case study is presented considering the implementation of pyrolysis plants for the recycling of ELT under the regulatory framework of the EPR Law. The results show that introducing political and technological parameters and variables into economic, environmental, and social objectives facilitates convergence towards a solution, despite the initial opposition of the objectives. Applying the ϵ-constraint method allows to find profitable alternatives for this project. However, those solutions that further reduce the gap and achieve a balance between the three objectives tend to produce negative economic outcomes, suggesting that fully sustainable scenarios may not be economically feasible. Sensitivity analyses highlight the trade-offs involved in balancing economic feasibility in sustainable scenarios with technological and regulatory measures. Considering all the above, it is necessary to strengthen regulatory policies that support reverse logistics, ELT recovery technologies, and the development of decentralized ELT management systems. Lastly, modifications in the collection goals, robust optimization for dealing with uncertainty, and multiple recycling technologies assessment are suggested as future guidelines. © 2025 Elsevier Ltd